Interplay of Work Culture and Work Motivation on Employee Satisfaction and Performance: A Study of Lampung Province Government Employees - Siregar, Syahrizal; Febriansyah (EAJ (Economic and Accounting Journal), 2024)
Civil Servant performance assessment aims to ensure objective employee development based on an achievement system and career system. Job satisfaction and good employee performance can be created if various influencing factors can be accommodated well and accepted by all employees. This research aims to examine the influence of culture and work motivation on the satisfaction and performance of Government employees at the Lampung Province Revenue Service. Data collection techniques in this research used questionnaires file research and interviews and data analysis techniques used in this research used descriptive analysis, questionnaire feasibility tests and structural equation analysis with data analysis using Structural Equation Modeling (SEM). The results of the research revealed that work culture and work motivation influence the level of job satisfaction, work culture and work motivation influence the performance of Government employees at the Lampung Province Revenue Service. This study provides evidence that a conducive work environment will have an impact on job satisfaction and employee performance. Keywords: Work Culture, Work Motivation, Job Satisfaction and Employee Performance